The temporal resolution of epibiont assemblages: Are they ecological snapshots or overexposures? - Rodland, David L.; Kowalewski, Michał; Carroll, Monica; Simões, Marcello Guimarães [UNESP] (University of Chicago Press, 2006)
The effects of time averaging on the fossil record of soft-substrate marine faunas have been investigated in great detail, but the temporal resolution of epibiont assemblages has been inferred only from limited-duration deployment experiments. Individually dated shells provide insight into the temporal resolution of epibiont assemblages and the taphonomic history of their hosts over decades to centuries. Epibiont abundance and richness were evaluated for 86 dated valves of the rhynchonelliform brachiopod Bouchardia rosea collected from the inner shelf. Maximum abundance occurred on shells less than 400 yr old, and maximum diversity was attained within a century. Taphonomic evidence does not support models of live-host colonization, net accumulation, or erasure of epibionts over time. Encrustation appears to have occurred during a brief interval between host death and burial, with no evidence of significant recolonization of exhumed shells. Epibiont assemblages of individually dated shells preserve ecological snapshots, despite host-shell time averaging, and may record long-term ecological changes or anthropogenic environmental changes. Unless the ages of individual shells are directly estimated, however, pooling shells of different ages artificially reduces the temporal resolution of their encrusting assemblages to that of their hosts, an artifact of analytical time averaging. © 2006 by The University of Chicago. All rights reserved.
Keywords: abundance; brachiopod; epibiont; fossil assemblage; species richness; taphonomy; Bouchardia rosea